Health Status After Cancer. Does It Matter Which Hospital You Belong To? - Jon H. Fiva; Torbjørn Hægeland; Marte Rønning (Statistics Norway, Research Department, 2009)
Survival rates are widely used to compare quality of health care. In this paper we introduce post-illness employment as a supplemental indicator of successful treatment of serious diseases. Utilizing rich register based data on cancer patients we document substantial differences across Norwegian hospital catchment areas with respect to employment five years after diagnosis. Conventional quality indicators based on survival rates indicate smaller differences. The two sets of indicators are only weakly correlated, suggesting that they capture different parts of the quality distribution, and that using only one of them may be insufficient.
Keywords: I11; I12; J21; 330; Quality indicators; health sector; survival; employment; cancer